Electrifying Africa - Bassam Fattouh; David Robinson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2018)
This issue of the Oxford Energy Forum focuses on the electrification of Africa, especially sub-Saharan Africa (SSA). Due to significant expected population growth, the number of Africans without electricity access in 2030 may not fall much from today's level of about 600 million, which is about 60 per cent of the world's current population without access to electricity. The articles cover a wide variety of countries and issues, focusing on barriers to meeting electrification objectives and ways to overcome them.
Keywords: 330